Kelayakan Investasi dan Pola Pengembangan UMKM Berbasis Desa Wisata - Putra Irwandi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Tourism villages are a government program designed to increase community potential and income based on local potential. The Barito Village area (Bambang, Bringin, and Pacokpicis) is a tourist village area still in development. Various activities carried out for the progress of the Barito Tourism Village Area are the establishment of economic destinations or MSMEs, which are expected to have an economic impact on community welfare and improve living standards. This research was carried out to provide an overview and direction to all parties in improving the welfare of the people of the Barito Village area through research formulations and objectives to analyze the feasibility of priority economic investments and determine the development pattern of Tourism Village-based MSMEs. The results of the identification carried out on the potential of existing MSMEs found 11 MSME units selected purposively from 58 samples. This research uses investment feasibility analysis, namely NPV (net present value), IRR value calculation, B/C ratio analysis, and payback period calculation. It analyzes descriptively in determining community-based development patterns for MSMEs. Based on the results that have been studied, five priority MSMEs forming the economy were obtained, which are suitable to continue sustainably because the NPV value is> 1. The IRR has a value greater than the existing interest rate. The BC ratio value is more than one, and the payback period follows the annual criteria: Biting Showroom, Barito Dairy Murni Industry, D'Ring Bringin Batik Showroom, The Rabbits of Barito, and Blacksmith Crafts. Meanwhile, the MSME development pattern is based on community-based development, which focuses on developing four aspects: growing economic aspects based on local wisdom, developing natural resource aspects, developing human resource aspects, and developing consumer or market development.